2017
DOI: 10.1371/journal.pmed.1002267
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological diagnoses and clinical correlates in older adults in Brazil: A cross-sectional study

Abstract: BackgroundClinicopathological studies are important in determining the brain lesions underlying dementia. Although almost 60% of individuals with dementia live in developing countries, few clinicopathological studies focus on these individuals. We investigated the frequency of neurodegenerative and vascular-related neuropathological lesions in 1,092 Brazilian admixed older adults, their correlation with cognitive and neuropsychiatric symptoms, and the accuracy of dementia subtype diagnosis.Methods and findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 103 publications
(141 reference statements)
3
121
2
10
Order By: Relevance
“…AD‐neuropathology was evaluated using the Consortium to Establish a Registry for Alzheimer’s disease (CERAD) criteria for neuritic plaques , and the Braak and Braak (BB) score for neurofibrillary tangles (NFT) . Our assessment of cerebrovascular lesions consisted of gross and microscopic evaluations . We registered infarcts by topography, type, stage, size and number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD‐neuropathology was evaluated using the Consortium to Establish a Registry for Alzheimer’s disease (CERAD) criteria for neuritic plaques , and the Braak and Braak (BB) score for neurofibrillary tangles (NFT) . Our assessment of cerebrovascular lesions consisted of gross and microscopic evaluations . We registered infarcts by topography, type, stage, size and number.…”
Section: Methodsmentioning
confidence: 99%
“…Using a well‐characterized, population‐based clinicopathological study from Brazil that features different race composition, socioeconomic factors, and educational attainment profile compared to available series from high‐income countries (HIC) , we demonstrated that even a small a percentage of African descent lower the relative risk to accumulate AD‐related neuritic plaques compared to Caucasian ancestry , suggesting that ethnicity may affect the vulnerability to neuropathological changes. Among other results retrieved from the same series, we also demonstrated that the prevalence of vascular dementia is higher in this population than in reported community‐based clinicopathological studies from HIC . Here, we sought to investigate the prevalence and impact on cognitive impairment of neuropathological changes in individuals aged 80 and older compared to a group aged from 50 to 79.…”
Section: Introductionmentioning
confidence: 99%
“…In AD, the microtubule-associated protein tau aggregates form neurofibrillary tangles (NFTs), one of the hallmark structural lesions of AD. Tau pathology is highly deleterious to synaptic function and is closely linked to cognitive decline [4,5]. The Braak and Braak staging scheme of neurofibrillary changes characterizes the stereotypic progression of regional deposition of NFT pathology from the brainstem and transentorhinal cortex, to the hippocampus, and finally to the association and primary cortices [6].…”
Section: Introductionmentioning
confidence: 99%
“…M ultiple age-related neuropathologies are increasingly recognized as contributors to dementia risk. [1][2][3][4][5][6] Although dementia is most commonly associated with Alzheimer's disease (AD) neuropathology, namely amyloid-beta plaques and neurofibrillary tangles, pure AD is relatively rare; the majority of dementia cases clinically diagnosed with probable AD show evidence of multiple neuropathologies. 4,[7][8][9][10][11] Even among pathologically confirmed AD cases, significant comorbidities are common and are frequently associated with worse clinical outcomes.…”
mentioning
confidence: 99%